An EFL Teacher’s Code Switching in a Young Learners’ Class - Lisa Khaerunnisa (Indonesian Journal of EFL and Linguistics, 2016)
This paper presents the results of a single case study of an EFL teacher’s code switching which involved three languages including English, Indonesian, and Javanese in a young learners’ class. More specifically, this qualitative study aimed to analyze the teacher’s types of code switching and functions of her code switching in the teaching and learning process. Data from classroom observations, teacher’s interview, students’ interview, and students’ questionnaire showed that all of the teacher’s code switching were conversational and based on the structure of her switching; she did inter-sentential, intra-sentential, and tag switching. Further, those different types of code switching served four positive functions for the EYL teaching. Those included strategy to deliver clear material explanations, strategy to deliver clear task instruction, strategy to give encouragement, and strategy for disciplining the students.